Implication of nutrition in severity of symptoms and treatments in quality of life in Parkinson’s disease: a systematic review - Mentxakatorre, Naia Ayo; Tijero, Beatriz; Acera, María Ángeles; Fernández-Valle, Tamara; Ruiz-Lopez, Marta; Gómez-Esteban, Juan Carlos; Del Pino, Rocio (Frontiers in Nutrition, 2024)
Parkinson's disease (PD) is characterized by motor and non-motor symptoms. Nutritional alterations are one of the non-motor symptoms that most influence the quality of life (QoL) in PD. This review aims to evaluate whether nutritional alterations are related either to the severity of motor and non-motor symptoms through the gut-brain axis or to the different treatments for PD and whether all of this, in turn, impacts the QoL of patients.A systematic review was carried out in MEDLINE and EMBASE databases, and Mendeley from 2000 to June 2024, searching for articles related to nutritional alterations in PD that alter patients' QoL.14 articles (2187 participants) of 924 records were included. Among the 14 studies examined, two investigated the relationship between nutritional status and QoL in patients with PD. Poor nutritional status was associated with lower QoL scores. Four studies explored the connection between nutritional status and its impact on both motor and non-motor symptoms (psychiatric disturbances, cognitive impairment, and fatigue), revealing a link between nutritional status, activities of daily living, and the severity of motor symptoms. Three studies identified changes in body weight associated with the severity of symptoms related to mobility issues in PD patients. Three studies investigated the relationship between different PD treatments and their interaction with changes in weight and energy metabolism, highlighting that weight loss in the early stages of PD needs adequate monitoring of different treatments, as well as the interaction between the central and peripheral nervous systems in regulating these processes. Finally, two studies investigated how gastrointestinal alterations and changes in the microbiota were related to cognitive status, thus identifying them as risk factors and early signs of PD. The systematic review highlighted the significant relationship between nutritional status and QoL in PD and how treatments of PD influenced in weight. An association was also observed in the gut-brain axis, where adequate nutritional status influenced the balance of intestinal microbiota, slowing cognitive decline, improving activities of daily living, and the QoL of PD patients. It is confirmed that the nutritional status of patients influenced both motor and non-motor symptoms of the disease, and therefore their QoL.